Laboratory capacity building for the International Health Regulations (IHR[2005]) in resource-poor countries: the experience of the African Field Epidemiology Network (AFENET) - Mukanga David; Nqobile Ndlovu; Masanza Monica; Gitta Sheba (BMC, 2010)
Abstract Laboratory is one of the core capacities that countries must develop for the implementation of the International Health Regulations (IHR[2005]) since laboratory services play a major role in all the key processes of detection, assessment, response, notification, and monitoring of events. While developed countries easily adapt their well-organized routine laboratory services, resource-limited countries need considerable capacity building as many gaps still exist. In this paper, we discuss some of the efforts made by the African Field Epidemiology Network (AFENET) in supporting laboratory capacity development in the Africa region. The efforts range from promoting graduate level training programs to building advanced technical, managerial and leadership skills to in-service short course training for peripheral laboratory staff. A number of specific projects focus on external quality assurance, basic laboratory information systems, strengthening laboratory management towards accreditation, equipment calibration, harmonization of training materials, networking and provision of pre-packaged laboratory kits to support outbreak investigation. Available evidence indicates a positive effect of these efforts on laboratory capacity in the region. However, many opportunities exist, especially to support the roll-out of these projects as well as attending to some additional critical areas such as biosafety and biosecuity. We conclude that AFENET's approach of strengthening national and sub-national systems provide a model that could be adopted in resource-limited settings such as sub-Saharan Africa.